Master of Medicine: Paediatrics and Child Health - Kabale University (Kabale University, 2022)
Child health related conditions account for a significant amount of the disease burden in south western Uganda where Kigezi region and Kabale University are situated. This area also adjourns boundaries with Congo Rwanda and generally has poor health indicators manly resulting from largely preventable diseases and conditions. The region though relatively large (over 2 million population) has less than 10 Paediatricians which situation has greatly affected improvements in newborn and child health care. This programme will therefore train and equip Paediatricians to competently meet the child health needs of communities within the region and beyond. The training will be done in rural Uganda and this practically helps the postgraduates to directly experience the challenges of child health within the communities. The overall goal of the Master of Medicine in Paediatrics and Child Health programme is to train a competent specialist in the practice of Paediatrics and Child Health and research. The graduate should be able to manage and organize Paediatric and Child Health services for communities with ability to mentor, train and supervise other health workers.